PENGARUH HEDONIC SHOPPING MOTIVATION, MERCHANDISING, DAN STORE ENVIRONMENT TERHADAP IMPULSE BUYING KONSUMEN DI ALFAMART SIDOMULYO SLEMAN - Setio Putranto, Angga (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
This study intends to find the impact of hedonic shopping motivation, merchandising, and store environment on consumer impulse buying at Alfamart Sidomoyo Sleman either partially or simultaneously. This research is a quantitative research with multiple linear regression analysis technique which is carried out using the SPSS program. Collecting data using a questionnaire, a sample of 100 respondents from Alfamart Sidomoyo Sleman consumers. The results of this study concluded that partially hedonic shopping motivation, merchandising, and store environment have a positive impact on impulse buying. Simultaneously the impact of hedonic shopping motivation, merchandising, and store environment has a significant impact on impulse buying, with a calculated F value of 22.885 and a sig value. 0.000 <0.05, while the adjusted R square is 39.9%.